Incidence of Severe Pain in Newly Diagnosed Ambulatory Patients with Stage IV Cancer. (2012) - Isaac, Thomas; Stuver, Sherri O; Davis, Roger B; Block, Susan; Weeks, Jane C; Berry, Donna L; Weingart, Saul N
Abstract : BACKGROUND: Pain is common among cancer patients. OBJECTIVE: To characterize the incidence of severe pain among newly diagnosed patients with stage IV cancer in ambulatory care. METHODS: A retrospective cohort of 505 ambulatory oncology patients with newly diagnosed stage IV solid tumours at a comprehensive cancer centre (Dana-Farber Cancer Institute, Boston, Massachusetts, USA) was followed from January 1, 2004, to December 31, 2006. Pain intensity scores were extracted from electronic medical records. The incidence of severe pain was calculated using the maximum monthly pain scores reported at outpatient visits. RESULTS: Of the 505 patients included in the present study, 340 (67.3%) were pain-free at the initial visit, 90 (17.8%) experienced mild pain, 48 (9.5%) experienced moderate pain and 27 (5.4%) experienced severe pain. At least one episode of severe pain within one year of diagnosis was reported by 29.1% of patients. Patients with head and neck, gastrointestinal and thoracic malignancies were more likely to experience severe pain compared with patients with other types of cancer (52.6%, 33.9% and 30.5%, respectively). In the multivariable model, patients whose primary language was not English (OR 2.90 [95% CI 1.08 to 7.80]), patients who reported severe pain at the initial visit (OR 9.30 [95% CI 3.72 to 23.23]) and patients with head and neck (OR 10.17 [95% CI 2.87 to 36.00]) or gastrointestinal (OR 4.05 [95% CI 1.23 to 13.35]) cancers were more likely to report severe pain in the following year. CONCLUSIONS: The incidence of severe pain was high in ambulatory patients with newly diagnosed stage IV cancer.